Exploiting island shelf resources - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1991)
Wheat genetic resources meeting diverse needs, edited by J P Srivastava and A B Damania 1990 391pp ISBN 0 471 92880